Pharmaceutical microbiology : a textbook - Goel, Nidhi (Oxford, U.K. : Alpha Science International, 2013)
PHARMACEUTICAL MICROBIOLOGY: A Textbook provides concise yet wide ranging views on important aspects of microbiology for students pursuing undergraduate courses in pharmacy, dental, medical and science departments.
Includes bibliographical references and index.
Keywords: Anti-infective agents